Analysis of the Feasibility of the Sasak Folktale of Dewi Anjani as Indonesian Language Teaching Material in Strengthening Cultural Literacy - Gita Sarwadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the suitability of the Sasak folktale Dewi Anjani as an Indonesian language teaching material in strengthening cultural literacy at the secondary school level. This research is motivated by the still limited use of local folktales as learning resources, even though folktales have great potential to develop literacy competencies while instilling cultural values ​​in students. The Dewi Anjani folktale was chosen because it represents the cultural identity of the Sasak people through religious, moral, social, leadership, environmental conservation, and respect for tradition values ​​that are still relevant to today's community life. The study used a qualitative approach with a descriptive method. Data were obtained through a documentation study of the Dewi Anjani folktale text and analyzed using content analysis techniques. The analysis of the feasibility of teaching materials refers to aspects of content, language, presentation, and graphics that are adjusted to Indonesian language learning outcomes and cultural literacy indicators. Data validity was carried out through theory triangulation and expert review. The results of the study indicate that the Dewi Anjani folktale meets the criteria as a suitable teaching material for use in Indonesian language learning. In terms of content, the story embodies authentic local cultural values ​​and supports the development of students' character. Linguistically, the language used is easy to understand and appropriate for the students' developmental level. The presentation, plot, characters, and conflict enhance student engagement in the learning process. Graphically, the story can be developed into engaging and contextual teaching materials. Utilizing the Dewi Anjani folktale not only supports the achievement of language and literary competencies but also strengthens cultural literacy through the recognition of local identity, the preservation of cultural heritage, and the fostering of an appreciation for regional culture. Therefore, the Dewi Anjani folktale is suitable as an innovative, contextual Indonesian language teaching material, oriented toward strengthening cultural literacy.